Education for public health 2030: transformation to meet health needs in a changing world - Sullivan, Lisa M.; Weist, Elizabeth M.; Barrington, Wendy E.; Fairchild, Amy L.; Hwang, Wenke; Kiviniemi, Marc T.; Mohammed, Shan D.; Wyant, Victoria A.; Alexander, Linda A.; Magaña, Laura (Frontiers in Public Health, 2023)
Education for public health is at a critical inflection point, and either transforms for success or fails to remain relevant. In 2020, the Association for Schools and Programs of Public Health launched an initiative, Framing the Future 2030: Education for Public Health (FTF 2030) to develop a resilient educational system for public health that promotes scientific inquiry, connects research, education, and practice, eliminates inequities, incorporates anti-racism, creates and sustains diverse and inclusive teaching and learning communities, and optimizes systems and resources to prepare graduates who are clearly recognizable for their population health perspectives, knowledge, skills, attitudes, and practices. Three expert panels: 1. Inclusive excellence through an anti-racism lens; 2. Transformative educational models and pedagogy; and 3. Expanding the reach, visibility, and impact of the field of academic public health are engaged in ongoing deliberations to generate recommendations to implement the necessary change. The article describes the panels’ work completed thus far, a consensus process guide, and work planned, including questions for self-evaluation, deliberation, and reflection towards actions that support academe in developing a resilient education system for public health, whether beginning or advancing through a process of change. The FTF 2030 steering committee asserts its strong commitment to structural and substantial change that strengthens academic public health as an essential component of a complex socio-political system. Lastly, all are called to join the effort as collaboration is essential to co-develop an educational system for public health that ensures health equity for all people, everywhere.